Tackling Racial Discrimination: Discussing Joe Biden and BTS Meeting on Anti-Asian Hate - Cyrilla Fathimatuzzahra; Zanuwar Hakim Atmantika; Galant Nanta Adhitya (Universitas 17 Agustus 1945 Surabaya, Prodi sastra Inggris, Fakultas Ilmu Budaya, 2022)
Human beings are created equal to each other, with the best form and we deserve to get good treatment from anyone and have the privilege to ask for that. Because life is only transitory, people should take advantage of every chance to achieve their goals. However, there is a group of people who hate it and end up treating some individuals from certain groups or races in a bad way. The research approach used in this study is qualitative, this article uses descriptive qualitative research which is simply a descriptive analysis or interpretation. The subjects in this article are American people who doing racism to the minority. It analyzes the racism of minorities, especially Asians, and the object of this article is racial discrimination. The article focuses on the presence of BTS and the White House Press Secretary, Karine Jean-Pierre at the White House meeting on 31 May 2022 in the context of AANHPI Heritage Month. The data sources used in this article are journals about racial discrimination and the BTS visit to the White House. In this discussion, the authors find discrimination by Americans against Asians and Asian descent, the attitude that Asians show when they experience racism, the invitation of BTS to the White House in the context of AANHPI Heritage Month, speeches of Joe Biden and BTS, and Karine Jean-Pierre's presence as White House Press Secretary.